EKSISTENSI PASAR SEBAGAI RUANG PUBLIK : Penelitian Pasar Kahayan Kota Palangka Raya - Handi K. Pratama; Joni Rusmanto (Prodi Sosiologi FISIP UPR, 2021)
In this modern era, the market is not only used as a place for transactions between traders and buyers, but there are many other functions of this traditional market. traditional market as a public space where there is no authoritarian power in the market and everyone is free to express opinions, where the market is also referred to as a public space and a place to interact and communicate. The method used in this research is qualitative. With data collection techniques through observation, interviews and documentation. The source of data used in this study is primary data in the form of interviews with key informants in the Kahayan market, Palangka Raya City. Data collection techniques used by researchers are direct observation, interviews and documentation. The results of this study aim to find out about how the Kahayan market has another function for the public sphere of the people of the city of Palangka Raya, not just a place for transactions or a place for buying and selling services. But there is still a function as a public space and a social function of the Kahayan market is indeed a public space that was built by the Palangka Raya city government for the needs of the community.